2016
DOI: 10.1177/0961203316628998
|View full text |Cite
|
Sign up to set email alerts
|

Drugs used in incident systemic lupus erythematosus – results from the Finnish nationwide register 2000–2007

Abstract: The objectives of the study were to examine the initial, first-year anti-rheumatic outpatient therapy in patients with incident SLE, as well as the concomitant use of drugs for certain comorbidities, compared to the use in the general population. The Finnish nationwide register data on special reimbursements for medication costs was screened to identify the inception cohort of 566 adult SLE patients (87% females, mean age 46.5 AE 15.9 years) over the years [2000][2001][2002][2003][2004][2005][2006][2007]. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In the present study, it was used in the treatment of almost 37% of SLE patients .The Saudi study reported comparable findings where third of patients received AZA [27], whereas it was used in very small number of Iraqi patients [35]. A European Finnish nationwide register data reported that 15% of their patients used AZA [22], whereas AZA is often preferred in Asia due to economic constraints and because of its safety in pregnancy [7].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the present study, it was used in the treatment of almost 37% of SLE patients .The Saudi study reported comparable findings where third of patients received AZA [27], whereas it was used in very small number of Iraqi patients [35]. A European Finnish nationwide register data reported that 15% of their patients used AZA [22], whereas AZA is often preferred in Asia due to economic constraints and because of its safety in pregnancy [7].…”
Section: Discussionsupporting
confidence: 59%
“…Saudi studies reported a similar finding where almost 100% of their SLE patients treated with HCQ [20,21]. Finnish nationwide register data reported that almost 73% of their patients were on HCQ [22]. AMs are also increasingly recognized as having beneficial effects beyond disease control and damage prevention, In particular it has a protective effect against thrombosis and loss of bone mass, It also improves lipid profiles and maternal outcomes during pregnancy [1,[23][24][25].…”
Section: Resultsmentioning
confidence: 74%
“…Hydroxychloroquinine has been shown to decrease prevalence of chronic kidney disease, and at least in Finland it is often used as the primary medicine in SLE treatment. 25,26 Another explanation for our result may be that almost all of our patients were native Finnish. SLE affects nervous system inducing neuropsychiatric disorders (neuropsychiatric SLE, NPSLE).…”
Section: Discussionmentioning
confidence: 85%
“…Medications for diabetes were used more often in the incident SLE cohort than in the general population OR 1.64 (1.20-2.45). Although glucocorticoids may induce diabetes, in this cohort exposure to glucocorticoids was of short duration (Elfving et al 2016). Data from the Toronto risk factor study on 250 SLE patients and controls showed an increased risk of DM in SLE patients (5% vs. 1%, RR = 6 (1.36-26.5)) (Bruce et al 2003).…”
Section: Diabetes and Slementioning
confidence: 81%